2010
DOI: 10.4137/cmo.s5228
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Invasive Aspergillosis in Neutropenic Patients. Comparison between Serum Galactomannan and Polymerase chain Reaction

Abstract: Background: Invasive aspergillosis (IA) is a major cause of morbidity and mortality in profoundly neutropenic patients, so early diagnosis is mandatory. Aim: Consecutive patients with hematological malignancies undergoing intensive chemotherapy were screened for IA with two different methods which were compared. Methods: From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Indeed, molecular methods are important alternatives to conventional methods, as they are sensitive and safe and can yield fast results [28]. In a study by Silva et al [29], IA was investigated, using PCR, in 1311 consecutive serum samples from 172 neutropenic patients, and by screening for the GM antigen in 806 consecutive serum samples from 169 neutropenic patients. The authors reported the sensitivity and specificity to be 75.0% and 91.9%, respectively, for PCR and 87.5% and 93.1%, respectively, for GM.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, molecular methods are important alternatives to conventional methods, as they are sensitive and safe and can yield fast results [28]. In a study by Silva et al [29], IA was investigated, using PCR, in 1311 consecutive serum samples from 172 neutropenic patients, and by screening for the GM antigen in 806 consecutive serum samples from 169 neutropenic patients. The authors reported the sensitivity and specificity to be 75.0% and 91.9%, respectively, for PCR and 87.5% and 93.1%, respectively, for GM.…”
Section: Discussionmentioning
confidence: 99%
“…1). Twentythree studies provided data for PCR based on the 2002 EORTC/ MSG criteria , and 14 did so by using the revised (2008) criteria (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…While an accurate diagnosis relies on histopathology, a lung biopsy is seldom performed and even in cases where it is feasible the diagnostic accuracy rarely exceeds 80%, more so in event of false negative results due to failure of the invasive method to reach the area infected by Aspergillus species. [22,23] Additionally, while Aspergillus hyphae can be readily differentiated from the wide, pauciseptate hyphae of mucoraceous moulds, distinguishing them from the narrow, septate hyphae of Fusarium and Scedosporium is often not possible. [11] Culture is time consuming and may delay the diagnosis of IPA.…”
Section: Discussionmentioning
confidence: 99%